Verification Of The Cause Of Pandemics Status Judgment In Contemporary Financial Transactions (Covid 19) Pandemic As A Model (Damascus University Journal for legal sciences, 2024)
This study reflects the position of Islamic jurisprudence on financial contracts, which prevented Corona pandemic from fulfilling and continuing its obligations. It reveals a number of flexible jurisprudence solutions to deal with the contractual damages caused by this pandemic by consolidating the principle of the status of pandemics in Islamic jurisprudence and revealing the cause of this principle and the reason for its legislation. The main objective of this research is to show the applicability of financial jurisprudence in times of pandemics and exceptional circumstances to financial transactions affected by the Corona pandemic; and to show that, the researcher used comparative analytical approach. This approach reached the conclusion that Corona epidemic was considered a health one, regulated by a set of jurisprudence provisions related to the situation of pandemics in majeure and exceptional circumstances
Keywords: Cause; Financial Transactions; Pandemic, Covid 19